The Role of Islamic Religious Education in Shaping Islamic Character Among Secondary School Students in Boyolali, Indonesia - Larasati, Indah; Ali, Mohamad (Institut Agama Islam An-Nawawi Purworejo, 2025)
This study explores the role of Islamic Religious Education in fostering Islamic character among students at SMPN 2 Boyolali. Employing a qualitative descriptive approach, data were collected through interviews, observations, and document analysis. Findings reveal that Islamic Religious Education contributes to character building through contextual teaching, habituation, extracurricular activities, exemplary practices, and disciplinary measures. Supporting and hindering factors are also discussed. This study contributes to the discourse on Islamic education's role in character development.